Enhanced power generation from algal biomass using multi-anode membrane-less sediment microbial fuel cell - Taskan, Banu; Bakir, Merve; Taskan, Ergin (Wiley, 2021)
In this study, a multi-anode sediment microbial fuel cell (SMFC) was used to investigate the electricity generation capacity of mixed-culture algae biomass. A multi-anode reactor configuration was used, which had tin-coated copper mesh (TCCM) anode and platinum-coated titanium mesh cathode. The SMFC produced a high-power density of 2965 mW/m(2), which is the highest power density reported in SMFC studies so far. The microscopic observations and gene profiling analysis confirmed that the biocompatibility of TCCM favors the bacterial adhesion and enrichment of electroactive bacterial groups (Gammaproteobacteria,Deltaproteobacteria, andAlphaproteobacteria). Our findings indicated that algae biomass could be used as an appropriate feedstock in SMFC to significantly improve electricity generation.
Keywords: 16 seconds rRNA; algal biomass; biofilm; multi-anode; sediment microbial fuel cell